Efficient robust fluorite CeZrO4-delta oxide catalyst for the eco-benign synthesis of styrene - Periyasamy, Kaliyappan; Aswathy, Venugopalan T.; Kumar, Venugopal Ashok; Manikandan, Marimuthu; Shukla, Rakesh; Tyagi, Avesh K.; Raja, Thirumalaiswamy (RSC Advances, 2015)
In this work, we have reported CeO2, ZrO2, physically mixed (PH)-CeO2/ZrO2 and fluorite CeZrO4-delta oxides and their catalytic activities for the oxidative dehydrogenation (ODH) of ethyl benzene (EB) to styrene (ST) using molecular oxygen, air and carbon dioxide as oxidants. The catalysts were prepared by a gel-combustion method followed by calcination at 600 degrees C for 6 h and subjected to catalytic activity measurements. All the catalysts were characterized and studied by various physicochemical methods. The reaction parameters were varied systematically such as different catalysts, oxidants, temperatures, EB flow and oxidant flow. CeZrO4-delta accounted for a 47% styrene yield for 72 h without any significant deactivation under optimized reaction conditions. A thorough analysis of the spent catalysts demonstrated the robustness of the catalyst for this reaction under different oxidants and reaction conditions. Pristine CeO2 deactivated easily and the activity decreased with time on stream of the reaction.

Palladium supported on fluorite structured redox CeZrO4-δ for heterogeneous suzuki coupling in water: a green protocol - Burange, Anand S.; Shukla, Rakesh; Tyagi, Avesh Kumar; Gopinath, Chinnakonda S. (Chemistry Select, 2016)
Pd on redox CeZrO4-δ catalysts was prepared, characterized and their activity was evaluated for Suzuki coupling reaction in water under reflux condition. Fresh and reduced form of 5 % Pd (R−Pd5) on CeZrO4-δ catalyst exhibited 100 % conversion in 2.5 and 1 h, respectively. R−Pd5 shows significant activity for wide range of substrate compatibility and for less reactive aryl bromides too. The mechanistic investigations proved the important role of redox CeZrO4-δ support on the catalytic activity. It was observed that the presence of oxygen vacancy along with Ce3+ enhances the activity. 1 wt % Pd photodeposited on pre-reduced CeZrO4-δ support requires a mere 20 min. for 100 % conversion of Suzuki coupling. Effect of metal dispersion and particle size on catalytic activity is also discussed. High Pd dispersion with small particle size (4±1 nm), particle size preservation after reaction, strong metal-support interaction and no leaching fully suggest the heterogeneous mechanism is operative for Suzuki coupling on 1 wt % Pd photodeposited on reduced CeZrO4-δ support. Present work hints the possibility of achieving high conversion for Suzuki reaction with very small amount of Pd through better dispersion by taking advantage of redox support and in water.

Role of palladium crystallite size on CO oxidation over CeZrO 4-δ supported Pd catalysts - Burange, Anand S.; Reddy, Kasala Prabhakr; Gopinath, Chinnakonda; Shukla, Rakesh; Tyagi, Avesh K. (Journal of Molecular Catalysis, 2018)
Photodeposited palladium on nanocrystalline CeZrO 4-δ support was evaluated for CO oxidation, as a function of particle size and pre-treatment. All the catalysts were well characterized by XRD, SEM, EDX, TEM, CO chemi-sorption and Raman spectroscopy. It was observed that change in photodeposition time alters the average crystallite size of Pd, and the same was confirmed by CO chemisorption. 7 nm average crystallite size of Pd exhibited excellent catalytic activity for CO oxidation. In order to understand the effect of support and metal-support interaction, 1 wt% Pd was deposited deliberately onto reduced and oxidized CeZrO 4-δ support. The reduced support with anionic vacancies and more Ce 3+ species exhibited an improvement in CO oxidation at onset temperature. Detailed analysis shows that Pd-deposition occurs preferentially at oxygen-vacancy sites and subsequent metal-support interaction influences the catalysis.

Protriptyline improves spatial memory and reduces oxidative damage by regulating NF kappa B-BDNF/CREB signaling axis in streptozotocin-induced rat model of Alzheimer's disease - Tiwari, Virendra; Mishra, Akanksha; Singh, Sonu; Mishra, Sandeep Kumar; Sahu, Kiran Kumari; Parul; Kulkarni, Mahesh J.; Shukla, Rakesh; Shukla, Shubha (Brain Research, 2021)
Antidepressants are well known to exert their role via upregulation of brain derived neurotrophic factor (BDNF). BDNF has been reported to exerts its neuroprotective effect in rodent and primate models as well as in patients of Alzheimer's disease (AD). The aim of our study was to evaluate the effect of protriptyline (PRT), a tricyclic antidepressant, in streptozotocin (STZ)- induced rat model of AD. Total 10 mu l of STZ was injected into each ventricle (1 mg/kg). PRT (10 mg/kg, i.p.) treatment was started 3-day post STZ administration and continued till 21 days. We found that STZ treatment significantly increased pTau, A beta 42 and BACE-1 expression, oxidative stress and neurodegeneration in hippocampus and cortex of adult rats. STZ induced impairment in spatial learning and retention memory was associated with increased WO and reduced CREB and BDNF expression in cortex and hippocampus. Interestingly, PRT treatment significantly reduced pTau, A beta 42 and BACE-1 levels, neurodegeneration, oxidative stress and glial activation, contributing to the improved spatial learning and retention memory in STZ treated rats. Moreover, PRT treatment significantly improved p-ERK/ERK ratio and enhanced BDNF and CREB levels by reducing NFXB and GFAP expression in STZ treated rats. Our data suggest that impaired NFXB and CREB signaling potentially contribute in AD pathogenesis by elevating oxidative stress and neuroinflammation mediated neurodegeneration. Our study has established protriptyline as a multi target molecule in pre-clinical model of AD and further investigations on PRT like molecules could pave way for further development of effective new treatments in neurodegenerative disorders.
Keywords: Alzheimer's disease; antidepressant; BDNF; Memory; Oxidative stress; Protriptyline